The Effect Of Vinyasa Yoga On Reducing The Intensity Of Primary Dysmenorrhoea In Adolescents Girl At MA Manbail Futuh - Utami, Aris Puji; Rahmawati, Eva Silviana; Sari, Novita (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: Primary dysmenorrhea is an important problem. In Indonesia, the prevalence of primary type dysmenorrhea in adolescent girls ranges from 60%-90%, while the remainder are sufferers of the secondary type (Astuti 2022). From the results of a preliminary study, it was found that 7 out of 10 teenage girls at MA Manbail Futuh experienced primary dysmenorrhea. If primary dysmenorrhea is not treated, it will affect the individual mentally and physically, so it is urgent to take immediate pharmacological and non-pharmacological action. Pharmacological treatment can cause side effects, so alternative non-pharmacological therapy is used, one of which is Vinyasa Yoga. Further research is needed to determine the effect of Vinyasa Yoga on reducing the intensity of primary dysmenorrhea pain. Method: The study used pre-experimental research with One group pretest-posttest design with 55 0f 64 respondents using a simple random sampling technique. Vinyasa Yoga is done at least 3 times for 1 month before menstruation and the instruments were questionnaires and numerical rating scales. Data analysis using the Wicoxon test. Result: The results of the research showed that all respondents experienced a decrease in pain intensity, the test results showed that p = 0.000, it was found that p <0.05, so H0 was rejected. This means that there is a significant effect of Vinyasa Yoga on reducing primary dysmenorrhea scores. Vinyasa yoga, which is done before menstruation regularly and correctly, trains the strength of the core muscles of the abdomen to relax so that it changes the pattern of receiving pain to a more calming pattern so that the intensity of the pain can be reduced.Conclusion : Abstract should be informative , and not only explain P value to show the difference t but also mention value of correlation or differences.